Does WeChat use intensity influence Chinese college students' mental health through social use of WeChat, entertainment use of WeChat, and bonding social capital? - Xia, Mengfan; Liu, Jing (Frontiers in Public Health, 2023)
Background Previous research notes that the usage of WeChat is significantly related to individuals' mental health, but the underlying mechanism is still not completely discovered. The present study aimed to explore the sequential mediating roles of WeChat use motivations and bonding social capital on the effects of WeChat use intensity on mental health in Chinese college students. Method The present study adopted an online survey with a total of 487 Chinese college students. Correlation analysis and serial mediation analysis were measured by process regarding the hypothesis. Results The study presented findings indicating that WeChat use intensity had both direct and indirect impacts on the levels of life satisfaction and loneliness experienced by college students in China. Specifically, the utilization of WeChat for social motivation and entertainment motivation was found to have a suppressive effect on the relationship between the intensity of WeChat usage and individuals' life satisfaction. The association between the intensity of WeChat usage and mental health outcomes (life satisfaction and loneliness) was found to be mediated by bonding social capital. Furthermore, the association between the intensity of WeChat usage and mental health was found to be mediated by the sequential mediation effects of using WeChat for social motivation and bonding social capital, as well as the sequential mediation effects of using WeChat for entertainment motivation and bonding social capital. Conclusion Our findings provide implications for policymakers and social workers regarding renovating the perceptions of the relationships between WeChat use intensity and overall mental health. Specifically, practical online activities and services of SNSs are recommended to be designed for meeting social and recreational gratifications and boosting bonding social capital, which in turn promotes psychological wellbeing.